Functional and radiological outcomes of distal humerus fractures treated with pre-contoured locking compression plate - Vanchi, Pravin K.; V., Raghav R.; M., Mohan Kumar (International Journal of Research in Orthopaedics, 2022)
Background: Distal humerus intra-articular fractures are one of the complicated fractures managed by orthopaedic surgeons. We did a prospective and a retrospective study on 21 patients with these fractures treated with pre-contoured locking compression plate. Methods: The 21 patients in this series were followed for a minimum of 1 year. The prospective study cases were followed at 3 months, 6 months and annually. The rating system of the Mayo elbow functional scoring system was used. The radiological evaluation was done using standard AP and lateral views. Results: We had 14 patients with range of motion of 50-100 degrees. There was only one patient with range of motion of <50 degrees. 6 patients had the maximum range motion of >100 degrees. We had 6 (23.57%) excellent, 9 (42.85%) good, 5 (23.80%) fair and 1 (4.7%) poor in the Mayo elbow scoring at the end of 1 year. We were able to compare our outcomes with a study done by Kumar et al done in 2017. They had 27 (89.66%) of excellent and good results as opposed to 27 (79.4%) in our study. Out of 21 patients in our study 17(80.95%) patients had good 11 (52.5%) / excellent 6 (28.5%) results. This was comparable with Jupiter et al. His study of 34 patients 26 (79.40/0) patients showed good 14 (41%) / excellent 13 (38.4%) result. Conclusions: Pre-contoured locking compression plate appears to be technically an ideal implant for comminuted osteoporotic bone providing an angle stable construct.